Aging changes 3D perception: Evidence for hemispheric rebalancing of lateralized processes. (May 2017) - Andrews, Bridget; d'Avossa, Giovanni; Sapir, Ayelet
Abstract: When judging the 3D shape of a shaded image, young observers assume that the light source is placed above and to the left. This leftward bias has been attributed to hemispheric lateralization or experiential factors. Since aging is associated with loss of hemispheric lateralization, in the current study we measured the effect of aging on the assumed light source direction. Older participants exhibited, on average, a decreased left bias compared to young participants, as well as greater within-group variability in the distribution of assumed light source directions. In a separate sample of young and old participants, we replicated the age related effect in the assumed light source direction. Furthermore, in both young and old participants the assumed light source direction and the lateralized bias in a line bisection task were correlated. These findings suggest that diminished hemispheric lateralization, which accompanies aging, may affect the perception of the 3D structure of shaded surfaces. Shape from shading may thus provide a simple behavioral tool to track age related changes in hemispheric organization. Highlights: When judging the shape of shaded images, we assume the light source to be on the left. This left bias may reflect lateralized processes, which are diminished in aging. We found a smaller left bias in old than young participants. The assumed light source direction was correlated with line bisection biases. Shape from shading may be used to track hemispheric lateralization.